2010
DOI: 10.1021/es101331j
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Kinetics of Antibiotics during Water Treatment with Potassium Permanganate

Abstract: The ubiquitous occurrence of antibiotics in aquatic environments raises concerns about potential adverse effects on aquatic ecology and human health, including the promotion of increased antibiotic resistance. This study examined the oxidation of three widely detected antibiotics (ciprofloxacin, lincomycin, and trimethoprim) by potassium permanganate [KMnO(4); Mn(VII)]. Reaction kinetics were described by second-order rate laws, with apparent second-order rate constants (k(2)) at pH 7 and 25 degrees C in the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
86
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(97 citation statements)
references
References 39 publications
7
86
2
2
Order By: Relevance
“…It is well documented that the pHdependence of the second-order rate constants between Mn(VII) and a large number of organic compounds generally increased with increasing pH, like phenol and lincomycin (Hu et al, 2010;Jiang et al, 2012), or had no obvious pH-dependence, like ciprofloxacin, carbamazepine, and dichlorvos (Hu et al, 2008(Hu et al, , 2010Liu et al, 2009). An opposite case is trimethopaim (Hu et al, 2010), where the second-order rate constants of the Mn(VII)/trimethopaim reaction decreased with increasing pH like those of the Mn(VII)/DCF reaction. This was attributed by the authors to the protonation of the nitrogen atom adjacent to the reacting site increasing the electron-withdrawing character of the amino group, which can in turn enhance the electrophilicity of the reaction site.…”
Section: Effect Of Phmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well documented that the pHdependence of the second-order rate constants between Mn(VII) and a large number of organic compounds generally increased with increasing pH, like phenol and lincomycin (Hu et al, 2010;Jiang et al, 2012), or had no obvious pH-dependence, like ciprofloxacin, carbamazepine, and dichlorvos (Hu et al, 2008(Hu et al, , 2010Liu et al, 2009). An opposite case is trimethopaim (Hu et al, 2010), where the second-order rate constants of the Mn(VII)/trimethopaim reaction decreased with increasing pH like those of the Mn(VII)/DCF reaction. This was attributed by the authors to the protonation of the nitrogen atom adjacent to the reacting site increasing the electron-withdrawing character of the amino group, which can in turn enhance the electrophilicity of the reaction site.…”
Section: Effect Of Phmentioning
confidence: 99%
“…Recently, a study demonstrated that Mn(VII) can effectively degrade carbamazepine (CBZ), with an electrophilic attack at the olefinic group in the central heterocyclic ring of CBZ, leading to the formation of a series of ring-opening oxidation products (Hu et al, 2008). In addition to CBZ, the degradation kinetics and mechanisms between Mn(VII) and three other widely used antibiotics were investigated, where the apparent second-order rate constants were reported to be 0.61 ± 0.02 M À1 s À1 (ciprofloxacin), 1.6 ± 0.1 M À1 s À1 (trimethoprim) and 3.6 ± 0.1 M À1 s À1 (lincomycin) at pH 7 and 25°C (Hu et al, 2010(Hu et al, , 2011. Hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX), a common groundwater contaminant, can be effectively transformed by Mn(VII) at both laboratory and field conditions, with a second-order rate constant 4.6 Â 10 À5 M À1 s À1 at pH 7 and 25°C (Chokejaroenrat et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Mn(VII) is attractive because its reduction product, MnO 2 , can act as coagulant/flocculant aid promoting physical removal of pollutants (Jiang et al, 2009;Ma et al, 1997;Zhang and Huang, 2003). Also, recent studies have shown that some pharmaceuticals (Hu et al, 2003(Hu et al, , 2009(Hu et al, , 2010(Hu et al, , 2011 and other micropollutants (Jiang et al, 2012;Zhang and Huang, 2003) can also react with potassium permanganate to produce several transformation by-products, whose ecotoxicological properties are still unknown. Yet, the reactivity of permanganate with several pharmaceuticals remains as an underinvestigated field, despite its common use in water treatment.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in China, the annual yield of cephalosporins in 2001 and 2010 was approximately 844 tons and 10,000 tons, respectively (Kümmerer, 2009;Xue and Chen, 2011). Similar to other kinds of antibiotics, cephalosporins cannot be absorbed and metabolized completely by the hosts (Hu et al, 2010). Hence large amount of cephalosporins are excreted via the urine and feces of animals and human beings (Junker et al, 2006).…”
Section: Introductionmentioning
confidence: 99%